1997
DOI: 10.1002/lt.500030202
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course of transplantation-associated de novo hepatitis B infection in the liver transplant recipient

Abstract: Transmission of hepatitis B infection from hepatitis B surface antigen (HBsAg)-negative antibody to hepatitis B core (anti-HBc)-positive liver donors has been previously described. The long-term outcome of these transplant-associated de novo hepatitis B patients has not been well described and may affect future use of donor organs that are anti-HBc-positive. We describe the experience in our first 332 transplants, performed before exclusion of anti-HBc-positive liver donors. Nine of these 332 (3%) donors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
121
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 30 publications
2
121
2
Order By: Relevance
“…Dickson et al 4 showed that 50% of infected patients had normal serum aminotransferase activities, and 85% had no or only mild inflammatory activity on liver biopsy. A relatively mild course was also noted in a series reported by Chazoulliéres et al, 6 Roche et al, 5 Douglas et al, 8 Liu et al, 13 Cavallari et al, 12 and Fabia et al 7 These data are in contrast to our experience. In this series, two clinical profiles were identified: (1) 4 patients developed de novo severe chronic hepatitis B, and histological follow-up suggests an accelerated natural history; and (2) 2 patients developed a fulminant hepatitis caused by de novo HBV infection.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…Dickson et al 4 showed that 50% of infected patients had normal serum aminotransferase activities, and 85% had no or only mild inflammatory activity on liver biopsy. A relatively mild course was also noted in a series reported by Chazoulliéres et al, 6 Roche et al, 5 Douglas et al, 8 Liu et al, 13 Cavallari et al, 12 and Fabia et al 7 These data are in contrast to our experience. In this series, two clinical profiles were identified: (1) 4 patients developed de novo severe chronic hepatitis B, and histological follow-up suggests an accelerated natural history; and (2) 2 patients developed a fulminant hepatitis caused by de novo HBV infection.…”
Section: Discussioncontrasting
confidence: 47%
“…[4][5][6][7][8][9][10][11][12][13][14]19 In our study, 6 HBsAg-negative patients of 136 liver transplant recipients (4.4%) who survived more than 3 months developed posttransplantation hepatitis B. The potential sources of HBV infection after OLT include liver and blood donors and hospital personnel; also, after OLT, intravenous drug abuse or sexual transmission can 6 With PCR technology, a possible source of viral infection was identified in another 2 patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The potential sources of the infection include transfused blood products, occult donor-organ infection and occult pretransplant infection in the recipient. Blood products are occasionally able to transmit HBV despite negative serological testing [14] or past HBV infection [15,161, with an estimated risk for the latter of 33%-78% [17,18,19,201. In the present case two possible sources of HBV infection were identified: sexual transmission from the HBsAg-positive partner or occult transmission from the HBcAb-positive liver donor.…”
Section: Discussionmentioning
confidence: 99%